2012
DOI: 10.1063/1.4742910
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent treatment of the local dielectric permittivity and electrostatic potential in solution for polarizable macromolecular force fields

Abstract: A self-consistent method is presented for the calculation of the local dielectric permittivity and electrostatic potential generated by a solute of arbitrary shape and charge distribution in a polar and polarizable liquid. The structure and dynamics behavior of the liquid at the solute/liquid interface determine the spatial variations of the density and the dielectric response. Emphasis here is on the treatment of the interface. The method is an extension of conventional methods used in continuum protein elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The orientational component is related to the static dielectric response of the interface, and an algorithm has been proposed to estimate it self-consistently in a continuum approximation. 72 The translational behavior is more complicated and is related to the mobility of water in the hydration shells. Recent simulations have shown that water in the second shell of a DNA molecule is more mobile than water in either the first shell or the bulk phase.…”
Section: Discussionmentioning
confidence: 99%
“…The orientational component is related to the static dielectric response of the interface, and an algorithm has been proposed to estimate it self-consistently in a continuum approximation. 72 The translational behavior is more complicated and is related to the mobility of water in the hydration shells. Recent simulations have shown that water in the second shell of a DNA molecule is more mobile than water in either the first shell or the bulk phase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, accuracy might be improved simply by moving away from the common practice of setting the dielectric cavity radii of atoms based only on their Lennard-Jones parameters, and instead accounting also for their partial charges or other determinants of local field strength. More advanced implicit solvent models, which seek to improve the physical description of the system 79,80 are also relevant in this context. In particular, variational implicitsolvent model (VISM) 81 and the geometric flow model 82,83 are inherently capable of altering the dielectric cavity radius as a function of field strength, and may therefore capture the solute electrostriction effect identified here.…”
Section: Discussionmentioning
confidence: 99%
“…These electrostatic effects of water exclusion are always present and traditionally described with the PB equation, e.g., by assigning a low dielectric permittivity to proteins and a high permittivity to water, or through a position-dependent permittivity, 3(r), if a more detailed representation of interfacial water is desired. 143,144 Other enthalpic effects of crowding are closely related to the solvent-induced forces (V s ) discussed in Section 3.2, due to the proximity of the interacting molecules to the crowders or conning surfaces; these effects can be quite intriguing and counter-intuitive, 103,123,145 potentially changing the usNP-protein interaction from attraction to repulsion.…”
Section: Crowding Forcesmentioning
confidence: 99%